DAKWAH DAN PENGEMBANGAN INTELEKTUALITAS - Muhtadin Dg. Mustafa (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2012)
Da'wah and intellectualism have a close relationship with each other. On one hand, Islamic preaching must be conveyed in a professional way, and on the other hand, it requires the incolvement of the intellecuals as a community at the forefront of missionary activity. There are two categories of intellectuals: first, Ulul Albab, the intellectuals who are able to draw conclusions, lessons and warnings from the Quran, historical events and phenomena. Second, ulama who has the same duties as the intellectual, whose task is to observe the whole teachings of Islam, interpret and convey them to the public, as well as to build a civilization. Intellectualis and Muslim scholars, both as the subject and object of Islamic preaching, is an interesting fact to be studied in order to create such packagings of Islamic preaching as materials, methods and media that are effective to establish the best people and happiness in the afterlife.